PEDAGOGICAL ASPECTS OF DIGITALIZATION OF EDUCATION - Sysoieva Svitlana (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article analyses the impact of globalization and technological development of society on research, education, organization and technology of the educational process. Pedagogical priorities of digitalization of education such as combining the efforts of scientists and practical specialists for a comprehensive analysis and interdisciplinary solution of modern problems of digital educational space and pedagogical principles of education digitalization have been identified. The article formulates the conceptual provisions of digital pedagogy and specification of the content of basic pedagogical concepts of digital education, development of digital didactics, revision of forms, methods, means and technologies of teaching, students' training and development in the digital space. The features and directions of education of children and youth in the digital space have been identified; new forms and methods of organizing the educational impact on children and youth in the digital environment have been revealed; the risks of digitalization of education and ways to overcome them have been outlined. The article shows that the mission of modern education is to provide society and every citizen with a proper transition to the digital age, focusing on other tools and different living environment and to prepare not only young but also middle-aged and older people for new types and kinds of work. An example of solving problems of digitalization of education, which requires joint efforts of scientists and practical specialists, is the creation and work of the Advisory Board on Digital Education and Pedagogy at the Department of General Pedagogy and Philosophy of Education of the NAES of Ukraine. Its functions are to examine current issues of digitalization of education in relation to interdisciplinarity: philosophical, theoretical and methodological, practical aspects of digital education and pedagogy; to сonduct in-depth research of the benefits and threats of digitalization of educational and scientific activities and to make analytical conclusions and recommendations for the management of education.